Respuesta :

Answer:

x = 5

Step-by-step explanation:

Simplifying

6x + -3 = 3x + 12

Reorder the terms:

-3 + 6x = 3x + 12

Reorder the terms:

-3 + 6x = 12 + 3x

Solving

-3 + 6x = 12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-3 + 6x + -3x = 12 + 3x + -3x

Combine like terms: 6x + -3x = 3x

-3 + 3x = 12 + 3x + -3x

Combine like terms: 3x + -3x = 0

-3 + 3x = 12 + 0

-3 + 3x = 12

Add '3' to each side of the equation.

-3 + 3 + 3x = 12 + 3

Combine like terms: -3 + 3 = 0

0 + 3x = 12 + 3

3x = 12 + 3

Combine like terms: 12 + 3 = 15

3x = 15

Divide each side by '3'.

x = 5

The answer is would me x=5
ACCESS MORE